Upaya Hukum Terhadap Perbuatan Wanprestasi dalam Perjanjian Pengikatan Jual Beli Tanah - Bintang Silado, Audrey; Syailendra, Moody R. (UNES Law Review, 2023)
The binding sale and purchase agreement is carried out with the aim of protecting the interests of the parties from acts of broken promises or default. Default is a situation where one of the bound parties is negligent or does not fulfill the obligations stipulated in the agreement. The problem in this research is the legal strength of the Sale and Purchase Agreement from a Civil Law perspective and how to resolve defaults in the Sale and Purchase Agreement on land. The aim of this research is to analyze the legal strength of binding sales and purchase agreements and to analyze legal remedies for resolving defaults in binding Sales and Purchase Agreements. The writing method used in this writing is normative. The research results show that the legal status of the Deed of Sale and Purchase Agreement as an initial agreement which is an authentic deed has perfect binding legal force and legal remedies for acts of default against PPJB can be carried out through litigation and non-litigation methods. The legal consequences of default are cancellation of the agreement, compensation, transfer of risk and payment of court costs.